Analisis Laju dan Kandungan Nutrien pada Sedimen di Instalasi Transplantasi Karang Metode Vertikal Pulau Samalona Kota Makassar - Noor, Rahmat Januar; Isman, Muhammad; Lapong, Muhammad Imran; Fathuddin, Fathuddin (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2024)
Samalona Island is a small island that administratively belongs to the inner zone of the Spermonde Islands region with low live coral cover. One effort to improve coral conditions is to carry out vertical transplantation, but hydro-oceanographic conditions are thought to be an inhibiting factor, including sediment. The research carried out aims to determine the suitability of oceanographic parameters, estimate sediment rates, and determine the phosphate and nitrate in sediments. The research method used a field experiment method by taking water and sediment samples and installing sediment traps for 15 days. The parameters measured in situ are temperature, pH, current speed, salinity, and dissolved oxygen, while the ex-situ test is the dry weight of sediment, TSS, nitrate, and phosphate concentrations. Data analysis uses descriptive statistics and is categorized according to the evaluation instrument used. The research results show that the values for temperature, pH, current speed, salinity, and dissolved oxygen meet the standard criteria for coral-based on PP 21/2022. The sediment rate during the research period was 0,003 – 0,015 gr/cm2/day, so it was categorized as having the potential damage to corals with a mild to severe impact level. The nitrate concentration in sediment ranges from 0,19 – 0,25 ppm while phosphate ranges from 0,35 – 0,72 ppm, so it can be said to be waters with a medium trophic level (mesotrophic). The current speeds and sediment rates potentially accelerate nutrient concentrations and cause sediment resuspension, thereby closing coral polyps, especially on corals closest to the substrate where vertical coral transplant installations are installed.